How Global is FDI? Evidence from the Analysis of Theil Indices - Frank Bickenbach; Wan-Hsin Liu; Peter Nunnenkamp (Empirical Economics, 2018)
It is open to question whether the intensified worldwide competition for FDI has reduced its traditionally strong concentration in a few large and relatively advanced host countries. We calculate and decompose Theil indices to track changes in absolute and relative concentration of FDI during the period 1970-2013. We find that both absolute and relative concentration decreased when excluding offshore financial centers from the overall sample. In addition to the narrowing gap between OECD and non-OECD countries, the concentration across non-OECD countries declined for both the absolute and relative measures. This is also true for major subgroups of non-OECD countries. Finally, recent developments indicate that low-income countries are no longer at the losing end of the competition for FDI.
Keywords: F21; 330; foreign direct investment; concentration; Theil decomposition